Global cosmetic industry (Advanstar Communications, 1999)
The information resource for personal care professionals.
Keywords: Cosmetics industry : Periodicals; Toilet preparations industry : Periodicals; Chemical industry : Periodicals; Pharmaceutical industry : Periodicals; Chemical Industry; Cosmetics; Chemical industry; Cosmetics industry; Pharmaceutical industry; Toilet preparations industry